2018
DOI: 10.1080/09168451.2017.1411775
|View full text |Cite
|
Sign up to set email alerts
|

The history and recent advances in research of polyprenol and its derivatives

Abstract: The reduction pathway leading to the formation of dolichol was clarified in 2010 with the identification of SRD5A3, which is the polyprenol reductase. The finding inspired us to reanalyze the length of the major chain of polyprenol and dolichol from several plant leaves, including mangrove plants, as well as from animal and fish livers by 2D-TLC. Polyprenol- and dolichol-derived metabolites such as polyprenylacetone and epoxydolichol were found together with rubber-like prenol. This review focuses on analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…The amount of polyisoprenoid content in the leaves and roots of B. cylindrica was between 0-182.35 mg/g with the most significant amount in the treatment of 0.5% and the smallest in the treatment of 2% to 0% in leaf tissues. This finding is in accordance with [11], [12], [13] reported that the content of polyisoprenoid alcohol was significantly increased in tissues during aging, especially the accumulation of polyisoprenoid in old leaf. Interestingly, polyisoprenoid contents increased exclusively in tissues that are resistant but not in susceptible plants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The amount of polyisoprenoid content in the leaves and roots of B. cylindrica was between 0-182.35 mg/g with the most significant amount in the treatment of 0.5% and the smallest in the treatment of 2% to 0% in leaf tissues. This finding is in accordance with [11], [12], [13] reported that the content of polyisoprenoid alcohol was significantly increased in tissues during aging, especially the accumulation of polyisoprenoid in old leaf. Interestingly, polyisoprenoid contents increased exclusively in tissues that are resistant but not in susceptible plants.…”
Section: Discussionsupporting
confidence: 92%
“…The difference in the length of the polyisoprenoid chain can be caused by several factors, including salinity stress factors, differences in the network of light effects and increased age or tissue aging [11], [12], [13], [14]. This circumstance may be part of the mechanism of the plant to survive salt stress [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although mangroves are well known to produce secondary metabolites including polyisoprenoid alcohols, the physiological function of these compounds remains to be elucidated (Basyuni et al 2016(Basyuni et al , 2017a(Basyuni et al , 2018a. Polyisoprenoid is a secondary metabolite compound with a linear polymer unit of five carbon chains found in almost all living cells (Swiezewska and Danikiewicz 2005;Sagami et al 2018). Our previous studies have shown that the salinity increased the triterpenoid content and triterpenoid synthase genes in mangrove seedlings (Basyuni et al 2009(Basyuni et al , 2012a.…”
Section: Introductionmentioning
confidence: 99%
“…Although mangroves are well known to produce secondary metabolites along with polyisoprenoid alcohols, the physiological function of these compounds remains poorly understood (Basyuni et al 2016(Basyuni et al , 2017a(Basyuni et al , 2018a. Polyisoprenoid is a secondary metabolite compound with a linear polymer unit of five carbon chains found in almost all living cells (Swierzewski and Danikiewicz 2005;Basyuni et al 2016Basyuni et al , 2017bBasyuni et al , 2018aSagami et al 2018). Our previous studies have shown that salinity enhanced the triterpenoid content and triterpenoid synthase genes in mangrove seedlings (Basyuni et al 2009(Basyuni et al , 2012a.…”
Section: Introductionmentioning
confidence: 99%